Three zutot - Weiss, Benjamin; Glasner, Eli (Topological Methods in Nonlinear Analysis, 2016)
Three topics in dynamical systems are discussed. First we deal with cascades and solve two open problems concerning, respectively, product recurrence, and uniformly rigid actions. Next we provide a new example that displays some unexpected properties of strictly ergodic actions of non-amenable groups.